pheSAG Based Rapid and Efficient Markerless Mutagenesis in Methylotuvimicrobium - Liu, Yongchuang; He, Xiangrong; Zhu, Pingping; Cheng, Minggen; Hong, Qing; Yan, Xin (Frontiers in Microbiology, 2020)
Due to their fast growth rate and robustness, some haloalkalitolerant methanotrophs from the genus Methylotuvimicrobium have recently become not only promising biocatalysts for methane conversion but also favorable materials for obtaining fundamental knowledge on methanotrophs. Here, to realize unmarked genome modification in Methylotuvimicrobium bacteria, a counterselectable marker (CSM) was developed based on pheS, which encodes the α-subunit of phenylalanyl-tRNA synthetase. Two-point mutations (T252A and A306G) were introduced into PheS in Methylotuvimicrobium buryatense 5GB1C, generating PheSAG, which can recognize p-chloro-phenylalanine (p-Cl-Phe) as a substrate. Theoretically, the expression of PheSAG in a cell will result in the incorporation of p-Cl-Phe into proteins, leading to cell death. The Ptac promoter and the ribosome-binding site region of mmoX were employed to control pheSAG, producing the pheSAG-3 CSM. M. buryatense 5GB1C harboring pheSAG-3 was extremely sensitive to 0.5 mM p-Cl-Phe. Then, a positive and counterselection cassette, PZ (only 1.5 kb in length), was constructed by combining pheSAG-3 and the zeocin resistance gene. A PZ- and PCR-based strategy was used to create the unmarked deletion of glgA1 or the whole smmo operon in M. buryatense 5GB1C and Methylotuvimicrobium alcaliphilum 20Z. The positive rates were over 92%, and the process could be accomplished in as few as eight days.